CFAP65 is required in the acrosome biogenesis and mitochondrial sheath assembly during spermiogenesis. Issue 23 (7th July 2021) - Wang, Weili; Tian, Shixong; Nie, Hongchuan; Tu, Chaofeng; Liu, Chunyu; Li, Yong; Li, Dongyan; Yang, Xiaoxuan; Meng, Lanlan; Hu, Tongyao; Zhang, Qianjun; Du, Juan; et al.
Abstract: Asthenoteratospermia is a common cause of male infertility. Recent studies have revealed that CFAP65 mutations lead to severe asthenoteratospermia due to acrosome hypoplasia and flagellum malformations. However, the molecular mechanism underlying CFAP65-associated sperm malformation is largely unclear. Here, we initially examined the role of CFAP65 during spermiogenesis using Cfap65 knockout (Cfap65 −/− ) mice. The results showed that Cfap65 −/− male mice exhibited severe asthenoteratospermia characterized by morphologically defective sperm heads and flagella. In Cfap65 −/− mouse testes, hyper-constricted sperm heads were apparent in step 9 spermatids accompanied by abnormal manchette development, and acrosome biogenesis was abnormal in the maturation phase. Moreover, subsequent flagellar elongation was also severely affected and characterized by disrupted assembly of the mitochondrial sheath (MS) in Cfap65 −/− male mice. Furthermore, the proteomic analysis revealed that the proteostatic system during acrosome formation, manchette organization and MS assembly was disrupted when CFAP65 was lost. Importantly, endogenous immunoprecipitation and immunostaining experiments revealed that CFAP65 may form a cytoplasmic protein network comprising MNS1, RSPH1, TPPP2, ZPBP1 and SPACA1. Overall, these findings provide insights into the complex molecular mechanisms of spermiogenesis by uncovering the essential roles of CFAP65 during sperm head shaping, acrosome biogenesis and MS assembly.